Pemberdayaan Masjid “Pembentukan Program Keluarga Sakinah Berkelanjutan di Masjid Darussalam” - Mochammad Arifin; Erdi Auliya Azzahra (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
Empowerment of mosques involves revitalizing their functions, roles, or activities to extend beyond individual acts of worship. This empowerment aims to be conceptualized, implemented, and sustained across religious, educational, and social service domains. Particular attention must be given to family-related aspects, considering the increasing issues in family resilience, which no longer stem solely from economic factors. Concerns such as underage marriages contrary to legal regulations, domestic violence, disputes over shared assets, inheritance, guardianship, and social services like zakat, infaq, sadaqah, and waqf are prevalent. These issues fall within the scope of Islamic Family Law, emphasizing the urgent need for its development as a solution aligned with the goals of mosque empowerment.Masjid Darussalam, located in Doko Village, Doko Sub-district, Blitar Regency, has conducted numerous socio-religious activities. However, these activities have yet to address aspects related to the "Sakinah Family" program. This indicates that the mosque's management requires additional expertise, knowledge, and technical skills to enhance their religious outreach efforts. If successfully realized, this initiative would provide significant added value. Therefore, the community service team will offer theoretical knowledge, practical experience, and introduce digitalization as a tool for religious outreach and a control center for the digital community, particularly within Masjid Darussalam’s environment.The primary objective of this community service initiative is to develop Islamic Family Law through a program called POSHKI (Islamic Family Law Development Post), which includes establishing a "Sakinah Family" program and digitalizing religious outreach efforts. The expected outcome of this mosque-based community service initiative is to serve as a learning platform, particularly for students of the Islamic Family Law Program at UNU Blitar, ensuring sustainability and publication in community service journals.